The Effect of Feed Rate Variation and Cooling on the Drilling Process of Carbon Fiber and Glass Fiber Composites - Reyhan, Rhesa Rama; Andoko , Andoko; Prasetya, Riduwan (PT Mattawang Mediatama Solution, 2024)
Carbon Fiber Reinforced Polymer (CFRP) and Glass Fiber Reinforced Polymer (GFRP) composites have extensive applications in the automotive, aerospace, and manufacturing industries due to their high strength and lightweight properties. However, machining processes such as drilling often encounter challenges such as delamination and tool wear due to the anisotropic nature and low thermal conductivity of these materials. This study evaluates the effect of varying feed rates and cooling methods on drilling quality and delamination levels in CFRP and GFRP composites. The cooling methods tested include dry, nanofluid, and cryogenic cooling. Experimental results indicate that cryogenic cooling produces the best hole quality with the lowest delamination levels, even at high feed rates. These findings provide valuable insights into the interaction between machining parameters and cooling methods, offering solutions to enhance the efficiency and quality of composite drilling processes in the manufacturing industry